Regulating Foreign Investment in a Diversifying Asia: A Comparative Analysis (TSUL LEGAL REPORT, 2026)
Foreign direct investment (FDI) has played a pivotal role in Asia’s remarkable economic growth and transformation over the past few decades. However, the region’s growing diversity in terms of economic development, political systems, and cultural values has also raised concerns about the potential negative impacts of FDI, such as environmental degradation, labor exploitation, and erosion of cultural identity. In response to these concerns, many Asian governments have implemented various regulatory measures to manage FDI flows and safeguard their national interests. This paper conducts a comparative analysis of FDI regulatory frameworks in a diverse sample of Asian countries, including India. The analysis examines the key objectives, instruments, and effectiveness of these regulatory frameworks in promoting sustainable and inclusive development. It also identifies common challenges and emerging trends in FDI regulation across the region. The findings of the study reveal a wide range of approaches to FDI regulation in Asia, reflecting the specific contexts and development priorities of each country. While some countries have adopted more liberal and open investment policies, others have maintained stricter controls to protect strategic sectors and promote domestic industries. The effectiveness of these regulatory frameworks has also varied, with some countries experiencing significant benefits from FDI while others have faced challenges in managing its potential negative impacts.